2017
DOI: 10.5851/kosfa.2017.37.4.494
|View full text |Cite
|
Sign up to set email alerts
|

Microbial, Physicochemical, and Sensory Characteristics of Quality Grade 2 Beef Enhanced by Injection of Pineapple Concentrate and Honey

Abstract: This study investigated the effect of injecting pineapple concentrate and honey into low marbled beef in order to enhance its sensory qualities, particularly tenderness and flavor, without compromising its fresh appearance. Beef loin was injected with a solution of 6.0% pineapple concentrate, 2.5% honey, 0.5% monosodium L-glutamate, 0.5% phosphate, and 0.3% salt (w/w) to 120% (w/w) of initial meat weight and stored for 14 d. Non-injected beef loin served as a control. Total aerobic bacterial counts, surface me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Similarly, no significant differences in tenderness, juiciness, or flavor were observed in the LM of Purunã bulls fed on diets containing up to 18% glycerin [ 38 ]. Sensory traits, including tenderness, are positively related to the intramuscular fat content in cattle [ 39 ]. Thus, the lack of an effect of glycerol inclusion on the intramuscular fat content may partly explain the absence of differences in sensory traits between the two groups in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, no significant differences in tenderness, juiciness, or flavor were observed in the LM of Purunã bulls fed on diets containing up to 18% glycerin [ 38 ]. Sensory traits, including tenderness, are positively related to the intramuscular fat content in cattle [ 39 ]. Thus, the lack of an effect of glycerol inclusion on the intramuscular fat content may partly explain the absence of differences in sensory traits between the two groups in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] To improve the tenderness and juiciness of fresh meat, injection of solutions containing salt, phosphate, and additional flavor components is commonly used as a marination process. [11] This method induces relatively rapid enhancements in sensory qualities and other functionalities. Recently, Seol et al [9] showed that injection (80 ppm) of Hanwoo beef with a proteolytic enzyme (thermolysin) and storage at 5°C for 3 days generated potent bioactive peptides with various activities, including ACE inhibitory and antioxidative activities.…”
Section: Introductionmentioning
confidence: 99%
“…(a) RP-HPLC profile and (b) ACE inhibitory activity of fraction E2-FIII. Peaks were divided into 17 groups(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and their ACE inhibitory activity was measured.…”
mentioning
confidence: 99%